Histomorphometric Evidences of the Effects of Allium Sativum on Cyclophosphamide Induced Testicular Toxicity in Adult Wistar Rat - Aende T. T; Beega P. I; Akunna G. G; Saalu L. C. (Innovation in Science and Technology, 2024)
Cyclophosphamide (CYP) is a widely used anticancer drug that can also induce testicular toxicity, hence male factor infertility. This adverse effect of CYP can be ameliorated by the antioxidant effect of garlic oil. This research work investigated the effects of Garlic oil (GO) on CYP-induced testicular toxicity in Adult Male Wistar rats. Thirty-six adult male Wistar rats were divided into 12 groups, each containing three (3) rats. Groups 1 and 2 were treated for 21 and 28 days respectively using 2mg/kg/BW of Normal saline. Groups 3 and 4 were treated for 21 and 28 days respectively using 90mg/kg/day of GO. Groups 5 and 6 were treated for 21 and 28days respectively with CYP (50mg/kg/wk). Groups 7 and 8 were treated for 21 and 28 days respectively with both GO (90/kg/day) and CYP (50/kg/wk). Groups 9 and 10 were treated for 21 days and 28 days respectively with GO (60mg/kg/day) and CYP (50mg/kg/wk). Groups 11 and 12 were treated for 21 and 28 days respectively using GO (30mg/kg/day) and CYP (50mg/kg/wk). The animals were sacrificed 24 hours after the last treatment by decapitation. The testes were harvested and processed for H&E staining. The values were presented as means of standard error of means (SAM). Statistical analysis was carried out using one-way analysis of variance (ANOVA). The result showed significant (p≤0.05) decrease in the final body weight of rats treated with only CYP. Histology findings in CYP alone groups (5 and 6) were that of seminiferous tubular atrophy and differential germ cell disorganization. The result from this study also revealed a significant (p≤0.05) decrease in normal sperm morphology and significant increase in abnormal morphology in both acute and chronic administration of CYP. This study has generated data showing that CYP disrupts redox balance in testicular tissues and thereby impair testicular histology. Importantly, it has been demonstrated that GO ameliorates these harmful effects of CP on reproductive function.